2011
DOI: 10.1007/s11269-011-9943-6
|View full text |Cite
|
Sign up to set email alerts
|

Modeling Groundwater Flow and Seawater Intrusion in the Coastal Aquifer of Wadi Ham, UAE

Abstract: Groundwater pumping from Kalbha and Fujairah coastal aquifer of the United Arab Emirates (UAE) has increased significantly during the last two decades to meet the agriculture water demands. Due to the lack of natural replenishment from rainfall and the excessive pumping, groundwater levels have declined significantly causing an intrusion of seawater in the coastal aquifer of Wadi Ham. As a result, many pumping wells in the coastal zone have been terminated and a number of farms have been abandoned. In this pap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
30
0
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 99 publications
(34 citation statements)
references
References 34 publications
2
30
0
2
Order By: Relevance
“…In coastal areas, up to one billion people utilize groundwater as the major source of drinking throughout the globe [7]. In such areas, seawater intrusion is the main environmental issue for contamination of groundwater [8][9][10]. The groundwater becomes unsuitable for domestic, irrigation as well as industrial purposes when mixed with salty water even in very small quantities [11].…”
Section: Introductionmentioning
confidence: 99%
“…In coastal areas, up to one billion people utilize groundwater as the major source of drinking throughout the globe [7]. In such areas, seawater intrusion is the main environmental issue for contamination of groundwater [8][9][10]. The groundwater becomes unsuitable for domestic, irrigation as well as industrial purposes when mixed with salty water even in very small quantities [11].…”
Section: Introductionmentioning
confidence: 99%
“…Groundwater models are commonly used to study coastal aquifers and to simulate and manage SWI (e.g. Ataie‐Ashtiani et al, , ; Ataie‐Ashtiani, ; Ataie‐Ashtiani and Ketabchi, ; Javadi et al, , Sherif et al ). Recently, a comprehensive review of the advances and future challenges of SWI processes, investigation, and management has been provided by Werner et al .…”
Section: Introductionmentioning
confidence: 99%
“…Seawater intrusion constitutes the main environmental problem facing coastal aquifers worldwide [6] [7]. It is shown that excessive groundwater exploitation in coastal area leads to seawater intrusion and influences the quality of the groundwater in aquifers [8] [9].…”
Section: Introductionmentioning
confidence: 99%